The Efficacy of Aquatic Therapy for Pain in Knee Osteoarthritis: A Systematic Review and Meta-Analysis - Rachmat, Ahdiyat Ananta; Wahyuni, Wahyuni (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Osteoarthritis (OA) is a joint disease that affects adults to the elderly in which the incidence and prevalence of OA will increase with age. One of the interventions to reduce pain for improving the quality of life in patients with knee osteoarthritis is by providing aquatic therapy. This study aims to determine the effectiveness of aquatic therapy for pain in patients with knee osteoarthritis.Subjects and Method: It was a metaanalysis study using PICO. P: patients with knee osteoarthritis. I: aquatic therapy. C: nonaquatic therapy. O: reduced pain. The articles used in this study were obtained from several databases namely Google Scholar, PubMed, NCBI, Science Direct, and Springer Link. The keywords used were